THE CONCEPTION OF POINT-RATING SYSTEM FOR ASSESSMENT OF STUDENTS' EDUCATIONAL RESULTS - Marina U. Prakhova; Svetlana V. Svetlakova; Nadezhda V. Zaichenko; Elena A. Khoroshavina; Andrey N. Krasnov (Высшее образование в России)
The assessment of student's learning outcomes is a very important component of educational process during the whole study period. This is an integrated index which describes not only student's knowledge level, but implicitly - the level of learning process organization and quality of teaching disciplines. The article considers the point-rating system (PRS) as one of the applicable quality evaluation systems in education. The Russian higher educational institutes started to use the point-rating system not long ago and very often its implementation makes some problems both to students and educators. The article aims to analyze these problems and to produce a general idea of application of PRS at technical higher educational institutions. The authors reveal the main reasons why the universities fail to use its advantages and sometimes even discredit it. The proposed PRS model has been approved by two departments of Ufa State Petroleum Technological University, which succeeded in using its pluses and minimizing its weak points. We managed to increase the effectiveness of the educational process and to provide some benefits to all members of the educational process -students, educators and potential employers.